Experiencias de aprendizaje en el desarrollo cognitivo de los niños de 2 a 3 años del centro de desarrollo infantil pedestal ubicado en la ciudad de Loja, período 2019-2020. - Sarango Pucha, Jessenia del Cisne (2021)
The following research work was based on the problem of the learning experiences used by the educators, its general objective was: To analyze the importance of learning experiences in the cognitive development of children from 2 to 3 years of age. The research design was non-experimental, the methods used to develop the study were: descriptive, analyticalsynthetic, deductive, and inductive, the instruments used for data collection were: the survey, observation, and the Bayley Child Development scale. This study arose from a macro project of the Early Childhood Education career, which made a diagnosis of 11 Child Development Centers in the city of Loja, for this research the CDI Pedestal was taken into account with a total of 6 teachers and 60 children, selecting 14 children and 3 teachers; the results obtained in the diagnosis showed that 50% of the children are in an inadequate rating in the mental scale and 79% in an inadequate level in the psychomotor scale. An activity guide composed of creative and innovative learning experiences was designed and delivered to the Child Development Center for its subsequent application in order to achieve in the child an integral development according to his age and to improve his cognitive growth. It is concluded that there is a great prevalence of problems in the cognitive development of the children where most of them presented an inadequate level of cognitive development and an inadequate level of psychomotor development, proving little fluency both in the perception of learning and in the sensorimotor coordination